Superdeformation in Pb isotopes with large neutron excess - Daoutidis, J.; Lalazissis, G. A. (HNPS Advances in Nuclear Physics, 2019)
Covariant Density Functional theory (CDFT) is used to investigate superdeformation in Pb isotopes on the neutron rich side of the periodic table. Energy surfaces and deformation parameters in this region are calculated by solving the constrained Relativistic Hartree Bogoliubov (RHB) equations. We use the parameter set DDME2, which has an explicit density dependence as well in the isoscalar as in the isovector channel together with the finite range pairing force DIS of Gogny. With increasing neutron number we find a characteristic pattern for superdeformed minima in these nuclei.